Determination of ammonia based on the electrochemical oxidation of N,N'-diphenyl-1,4-phenylenediamine in propylene carbonate. - Ji, X; Compton, R (2007)
The oxidation of N,N'-diphenyl-1,4-phenylenediamine (DPPD) has been studied by cyclic voltammetry at glassy carbon electrodes in propylene carbonate. Next, the reaction between ammonia and DPPD was similarly investigated. It has been shown that ammonia reversibly removes protons from oxidized DPPD molecules, thus facilitating the oxidative process with the emergence of a new wave at less positive potentials. The results suggest a novel methodology for the electrochemical determination of ammonia based on its interaction with DPPD in propylene carbonate. The measurement of the current of the new wave is shown to scale linearly with the ammonia concentration up to ca. 200 ppm and above.